Analisis Kontribusi Dan Efektivitas Penerimaan Pajak Daerah Dan Retribusi Daerah Pada Pendapatan Asli Daerah Kabupaten Bantul, Yogyakarta Tahun 2021-2024 - Prasetyo, Agung Slamet; Atalattof Santoso (Universitas Nusa Nipa Maumere, 2026)
This study aims to analyze the contribution and effectiveness of Local Tax and Local Retribution revenues to the Regional Original Revenue (PAD) of Bantul Regency during the 2021–2024 period. This research employs a quantitative descriptive approach using secondary data obtained from the Budget Realization Report (LRA) of Bantul Regency. The data analysis techniques used include contribution ratio analysis and effectiveness analysis by comparing realization with predetermined targets. The results show that the contribution of Local Taxes to the PAD of Bantul Regency during the 2021–2024 period is classified as good, with an average of 45.12%. Meanwhile, the contribution of Local Retribution to PAD is categorized as very low, with an average of 6.37%. In terms of effectiveness, Local Tax revenue is considered very effective with an average effectiveness rate of 109.18%, while Local Retribution revenue is categorized as quite effective with an average effectiveness of 92.42%. Based on these results, it can be concluded that Local Taxes are the most dominant and reliable source of PAD in Bantul Regency, while Local Retribution, although quite effective in achieving its targets, still requires optimization. Therefore, efforts are needed to optimize the collection of local retributions through the expansion of retribution objects, the review of more realistic targets, and the improvement of regional revenue management quality.